2021
DOI: 10.1177/1947603521994626
|View full text |Cite
|
Sign up to set email alerts
|

Talar and Subtalar T1ρ Relaxation Times in Limbs with and without Chronic Ankle Instability

Abstract: Objective The primary aim was to determine differences in talocrural and subtalar joint (STJ) articular cartilage composition, using T1ρ magnetic resonance imaging (MRI) relaxation times, between limbs in individuals with unilateral chronic ankle instability (CAI) and compare with an uninjured control. Our secondary purpose was to determine the association between talocrural and STJ composition in limbs with and without CAI. Design T1ρ MRI relaxation times were collected on 15 CAI (11 females, 21.13 ± 1.81 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Although the cumulative literature within the lower extremity shows a consistent relationship between lower loading characteristics and greater T1ρ relaxation times, it is unclear why the associations were seen in the subtalar joint but not the talar dome. We believe this is likely due to the fact that (i) talar and subtalar T1ρ relaxation times do not associate in individuals with CAI (13) and (ii) that the normal shank–rearfoot coupling is disrupted in individuals with CAI (31). It is also possible that subtalar T1ρ relaxation times more closely align with loading-related variables because of the important role the subtalar joint plays in shock absorption (32).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the cumulative literature within the lower extremity shows a consistent relationship between lower loading characteristics and greater T1ρ relaxation times, it is unclear why the associations were seen in the subtalar joint but not the talar dome. We believe this is likely due to the fact that (i) talar and subtalar T1ρ relaxation times do not associate in individuals with CAI (13) and (ii) that the normal shank–rearfoot coupling is disrupted in individuals with CAI (31). It is also possible that subtalar T1ρ relaxation times more closely align with loading-related variables because of the important role the subtalar joint plays in shock absorption (32).…”
Section: Discussionmentioning
confidence: 98%
“…These increased talar accessory motions would occur concurrently with the large COP displacements during static stance (29) and result in shearing forces to the talar but not the subtalar cartilage. These increased talar but not subtalar accessory motions likely also contribute to the lack of talar and subtalar T1ρ relaxation time associations in individuals with CAI (13). It is less clear why association magnitudes are not consistent across postural control outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using magnetic resonance imaging (MRI) have demonstrated cartilage degeneration in talocrural and subtalar joint. Song et al demonstrated that patients with CLAI have lower proteoglycan content in both the talocrural and posterior subtalar joints compared to the contralateral and healthy control limbs using T1ρ MRI [20]. Kim et al compared T2 relaxation values in the subtalar joint cartilage between patients with CLAI and healthy volunteers, and CLAI showed significantly higher T2 relaxation values in the posterior subtalar joint [21].…”
Section: Discussionmentioning
confidence: 99%